Gamma irradiation: A Novel Approach to Mitigate Klebsiella pneumoniae Contamination in Seafood - Banavath, Srinu Nayak; Bojayanaik, Manjanaik; Chavan, Sachin Dnyanoba; Siravati, Maga Raju; Naik, Sagar Naik Chandra; Alandur, Veena Shetty; Hiriur, Somashekarappa (Fishery Technology, 2025)
Klebsiella pneumoniae, a known causative agent ofcommunity-acquired bacterial pneumonia, is an emerging pathogen associated with severe morbidity and mortality, particularly in newborns and immunocompromised individuals. Recent reports have indicated the presence of Klebsiella spp. in contaminated seafood, raising concerns about food safety. This investigation evaluated the radiation sensitivity of K. pneumoniae (ATCC 700603) in various seafood samples. The D10 values, representing the radiation dose required to achieve a one-log reduction in bacterial population, were determined in both saline and nutrient broth as 0.119±0.004 kGy and 0.1255±0.002 kGy, respectively. Seafood samples including shrimp, clams, and squid were experimentally contaminated with K. pneumoniae at a concentration of 6.85×108 cfu/g and exposed to gamma irradiation at incremental doses of 0, 1, 2, 3, and 4 kGy. The D10 values observed for K.pneumoniae in shrimp, clams, and squid were 0.1995±0.0015 kGy, 0.208±0.0019 kGy, and 0.2015±0.0005 kGy, respectively. Notably, no viableK. pneumoniae was recovered from samples treated with 3 kGy and stored at 4°C for 12 days, even after enrichment and selective plating. These results demonstrate that a gamma irradiation dose of 3 kGy  is effective for the complete elimination of K. pneumoniae in seafood, highlighting its potential application for enhancing seafood safety.